EXPLORING THE IMPACT OF GREEN FINANCING ON BANK STABILITY: INSIGHTS FROM INDONESIAN ISLAMIC AND CONVENTIONAL BANKS - Irfany, Mohammad Iqbal; Putri, Fatimah Iskandar; Haq, Daffa Aqomal (EL DINAR: Jurnal Keuangan dan Perbankan Syariah, 2024)
This study examines the influence of green financing on the efficiency of Islamic and conventional banks in Indonesia between 2016 and 2022. Employing the Data Envelopment Analysis (DEA) method to compute efficiency scores and Tobit regression to evaluate the impact of green financing, the findings reveal that conventional banks outperform their Islamic counterparts in terms of efficiency. This disparity is attributed to superior risk management practices and the benefits of operational scale. Notably, green financing enhances the efficiency of both banking types, with its effects being more pronounced in smaller banks. These insights underscore the potential of green financing to advance sustainability without undermining banking efficiency. The study advocates for robust policy frameworks to incentivize green financing initiatives, particularly targeting smaller banks, to maximize their role in fostering sustainable development.